Acid anhydrides and the unexpected N, N-diethylamides derived from the reaction of carboxylic acids with Ph3P/I2/Et3N. Issue 3 (20th January 2016) - Phakhodee, Wong; Duangkamol, Chuthamat; Wangngae, Sirilak; Pattarawarapan, Mookda
Graphical abstract: Abstract: The formation of acid anhydrides from the phosphorous-mediated activation of carboxylic acids was investigated. Under various systems, activation of benzoic acid in the presence of base led to the formation of benzoic anhydride at different rates depending on the reactivity of the reagents. Using the Ph3 P–I2 /Et3 N combination, most aryl acids were converted into the corresponding anhydrides in high yields within 5–10 min. However, for nitro-substituted derivatives, unexpectedly, N, N -diethylamides were isolated without anhydride formation. These results indicated the pronounced effect of substituents in governing these potential side reactions which can significantly affect the yields of acylation reactions promoted by phosphonium species.